Fenomenologi Peer Group di Kalangan Remaja - Fadilah Hayatun Nufus; Beti Malia Rahma Hidayati (Journal of Theory and Practice in Islamic Guidance and Counseling, 2025)
Every individual will definitely go through phases of life, especially adolescence, in this phase adolescents will search for their identity for a better survival, which this process will not be easy to go through so adolescents will need social encouragement from sources of support around them. Peer groups or peers have a great influence on adolescents to form their identity. Peer groups are a place where each individual feels recognized, gets sympathy and gets encouragement. But there are times when in the peer group environment adolescents will get pressure in it to be able to match the habits of the group. Therefore I made this article which discusses the influence of the peer group environment on adolescents because to more clearly know the other influences on adolescents. The author uses the library research method by collecting data or reports from the previous 5 years, to allow researchers to collect and analyze information scientifically, so that the results of the study can be based on strong empirical evidence.